The analysis of the parenting implications on the emotional closeness of parent-child improvement - Zadrian Ardi; Galang Zaki Aulia (RedWhite Press, 2020)
The development of science and knowledge and the structure of society has had various impacts on the order of social life. No exception influences the smallest organization, namely the family. The model and parenting patterns of the previous generation (the baby boomers’ generation) are significantly different from the next generation. Of course, this also causes differences in the results and impacts obtained. However, the issues related to parenting tend to remain the same. One parenting that is often used is authoritarian parenting, in which parent’s tom much impose his will on the child as desired. This makes children become depressed so that the proximity of the child with parents rift or loose. The purpose of this study is to analyze the implications of parenting conditions and its various characteristics in building closeness between parents and children.